2009
DOI: 10.1139/z09-111
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic rates and movements of the male tarantula Aphonopelma anax during the mating season

Abstract: Tarantulas exhibit sexual dimorphism in their resting metabolic rate (RMR). The significantly higher RMRs observed in sexually mature males may be an adaptive strategy to support their higher energetic demands when searching for females. In this study, we investigated how intrasexual differences in male RMR may affect their locomotory activity and behavior during the mating season. Over a 2-year period, we radio-tagged male Texas tan tarantulas ( Aphonopelma anax (Chamberlin, 1940)), measured their movements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
1
8
0
1
Order By: Relevance
“…In the other ambulation experiments with G. rosea , no sexual differences are found in A t , in agreement with the results reported for other spiders (Stoltey & Shillington, ), whereas, despite the high variability, d is significantly longer in males than in females, revealing a high tracking efficiency. This means that smaller males may travel longer distances.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the other ambulation experiments with G. rosea , no sexual differences are found in A t , in agreement with the results reported for other spiders (Stoltey & Shillington, ), whereas, despite the high variability, d is significantly longer in males than in females, revealing a high tracking efficiency. This means that smaller males may travel longer distances.…”
Section: Discussionsupporting
confidence: 91%
“…Janowski‐Bell & Horner () report that the Texas brown tarantula Aphonopelma hentzi may travel up to 95 m in 1 day, a result in contrast to that for G. rosea in 1 h of experimental trials. Stoltey & Shillington () report that males of A. anax (Texas tan tarantula) may travel 90–259 m in a day and do not find a relationship between M b and distance recorded by telemetry, which appears to be more consistent with the results for G. rosea . However, a negative M b relationship is found for G. rosea when the distance travelled by both males and females is included, which can be explained by the large body mass of females.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Like other burrowing tarantulas (Janowski-Bell and Horner 1999;Pérez-Miles et al 2005), males of the species are responsible for long-range gene dispersal, by walking large distances among female aggregations and crossing nonhabitat features such as roads (Shillington and Verrell 1997;Yáñez and Floater 2000;Pérez-Miles et al 2005). Although dispersal distances for B. vagans remain unknown, Stoltey and Shillington (2009) showed that males of Aphonopelma anax Chamberlin 1940 (Araneae, Theraphosidae) were capable of walking at a speed of 365 m/day, covering an area of up to 29 ha during the breeding season. In contrast, Janowski-Bell and Horner (1999) showed that A. hentzi Girard 1852 walks at a speed of 94.9 m/day.…”
Section: Introductionmentioning
confidence: 99%
“…Os estudos de V O 2 Max em aranhas é ainda mais complicado do que com vertebrados (Anderson & Prestwich, 1985;Shillington & Peterson, 2002;Stoltey & Shillington, 2009). Além da dificuldade experimental, no caso das aranhas a V O 2 Max pode não possuir o significado biológico desejado devido ao possível compromisso entre locomoção e trocas gasosas necessárias à respiração (Wilson & Bullock, 1973).…”
Section: Bioenergética De Aranhasunclassified